2020
DOI: 10.1186/s40748-020-00121-3
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Prevalence and associated factors of early initiation of breastfeeding among women delivered via Cesarean section in South Gondar zone hospitals Ethiopia, 2020

Abstract: Background Early initiation of breastfeeding is putting the newborn to breast within one hour after birth. This study was aimed to assess prevalence of early initiation of breastfeeding and its associated factors among mothers who delivered by cesarean section in South Gondar Zone hospitals Northwest Ethiopia, 2020. Methods An institutional based cross-sectional study was employed in South Gondar Zone hospitals from June 12 to July 03, 2020. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
(36 reference statements)
4
7
0
Order By: Relevance
“…Multiparous mothers could have a personal experience on the practice of timely initiation of breastfeeding while primiparous mothers are devoid of any personal experience. Our nding was supported by studies done in the South Gondar zone in Ethiopia and Sudan (16,52). This can be justi ed by the fact that multiparous mothers will have more information exposure regarding the importance of timely initiation of breastfeeding while receiving care at ANC, labor, and delivery or post-natal services.…”
Section: Discussionsupporting
confidence: 75%
“…Multiparous mothers could have a personal experience on the practice of timely initiation of breastfeeding while primiparous mothers are devoid of any personal experience. Our nding was supported by studies done in the South Gondar zone in Ethiopia and Sudan (16,52). This can be justi ed by the fact that multiparous mothers will have more information exposure regarding the importance of timely initiation of breastfeeding while receiving care at ANC, labor, and delivery or post-natal services.…”
Section: Discussionsupporting
confidence: 75%
“…Caregiver factors were mentioned by 75.0% (42 of 56) of studies, including 37 studies (66.1%) that described barriers [ 31 , 32 , 34 36 , 38 , 43 , 46 , 50 52 , 55 , 56 , 58 – 62 , 64 , 66 , 68 – 84 ] and 27 studies (48.2%) that described facilitators [ 32 , 37 , 38 , 43 , 44 , 46 , 48 , 49 , 51 , 55 , 58 , 60 , 61 , 68 , 69 , 71 76 , 79 – 82 , 84 , 85 ]. Frequently mentioned barriers included inadequate lactation counselling [ 32 , 34 , 43 , 52 , 72 , 79 ] and misconceptions [ 34 36 , 50 , 52 , 55 , 56 , 60 , 62 , 68 , 72 , 74 , 77 , 79 , 83 ], such as breastmilk alone would not meet nutritional needs for the baby, formula was healthier, colostrum was dirty or not real breastmilk, infants required water in hot weather or infants required rest after delivery.…”
Section: Resultsmentioning
confidence: 99%
“…A study from Malawi suggested that HIV-positive mothers saw exclusive breastfeeding as very demanding on their bodies and made them prone to develop AIDS faster [ 74 ]. Caesarean section and breast complications were also frequently mentioned challenges [ 34 , 38 , 51 , 52 , 71 , 72 , 78 , 83 ]. A study from Uganda found that caesarean delivery was associated with an over 8-fold rate of delayed initiation to breastfeeding (aOR 8.6, 95% CI: 4.7–16.0) [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the included studies, seven of them were from Amhara region [ 19 , 20 , 24 , 25 , 30 32 ], two studies from each of the following; Tigray [ 22 , 33 ], Oromo [ 34 , 35 ], South Nation Nationality and Peoples region (SNNPR) [ 18 , 36 ] and Ethiopian Demographic Health Survey (EDHS) data [ 21 , 26 ] while the remaining two studies were contributed from Addis Ababa [ 37 ] and Afar region [ 38 ] (one study for each). All eligible studies in this review were cross-sectional study design consisting 29,919 mothers as study participant.…”
Section: Resultsmentioning
confidence: 99%